PENERAPAN PSAK NO.34 PADA LAPORAN KEUANGAN PT. MULTI SARANA TEKNIK INDONESIA - Astutik, Mura Dia; Sapari, Sapari (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The research has been carried out on PT. Multi Sarana Teknik Indonesia. PT. Multi Saran Teknik Indonesia is a construction company which is located in Surabaya. This research is meant to find out the implementation of revenue and burden recognition which has been done by using the completion percentage method to the PSAK No. 34 (Revised 2010) about the contract of the construction in accordance with the financial statement on PT. Multi Sarana Teknik Indonesia. Qualitative method is applied in this research. Qualitative method is the method which focuses on logical thinking by making a selection among the formulation of the problem, the purpose, the technique, and the paradigm or the thinking concept in order to find out the meaning of the phenomenon. Qualitative method is meant to comprehend the phenomenon which has been experienced by the subject of the research. It can be concluded that PT. Multi Sarana Teknik Indonesia has not in accordance with the PSAK No. 34 (Revised 2010). Therefore, the researcher has made some journals to adjust the financial statement (the Balance Sheet & the Profit and Loss) based on the PSAK No. 34.Keywords: Income, Burden, Construction, Percentage of Completion Method.